Polyherbal Therapy and Ayurvedic Approaches for the Management of Poorly Controlled Type 2 Diabetes Mellitus in Elderly Patients - Resna Murti Wibowo; Syamsudin Syamsudin; Hesty Utami Ramadaniati; Probosuseno Probosuseno (Muhammadiyah Medical Journal, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder characterized by hyperglycemia resulting from abnormalities in insulin secretion, insulin action, or both. In 2021, there were 536.6 million cases of type 2 diabetes mellitus globally. Proper management of T2DM patients is essential to control blood glucose levels and prevent complications in other organs. The use of polyherbal containing Smallanthus sonchifolius, Syzygium polyanthum, Camellia sinensis, and Stevia rebaudiana helps treat T2DM patients. Case presentation: A 71-year-old male patient complained of frequent weakness, dizziness, blurred vision, chest discomfort, bloating, tremors in the hands, and tingling in both feet. Past medical history: hypertension, narrowing of blood vessels, and pancreatitis. The patient uses regular medication including nebivolol, amlodipine, atorvastatin, metformin, glimepiride, and neuralgic. The patient feels that the complaints come and go and feels depressed with a lot of medication and stomach discomfort. The patient wants herbal medicine for T2DM therapy. Conclusion: The patient was diagnosed with geriatric syndrome with poorly controlled type 2 diabetes mellitus, hypertension, cervical spondyloarthrosis, Parkinsonism, chronic pancreatitis, and dyslipidemia. The patient received routine treatment for 3 months with a combined polyherbal formulation and showed clinical and laboratory improvement in HbA1c from 8.3% to 6.8%.